Fungal Biosurfactants from Mortierella alpina - Baldeweg, Florian; Warncke, Paul; Fischer, Dagmar; Gressler, Markus (Organic Letters, 2019)
The zygomycete Mortierella alpina is a well-known producer of polyunsaturated fatty acids in the food industry. Two series of its secondary metabolites are reported: Malpinins, a family of amphiphilic acetylated hexapeptides, were chemically characterized and serve as natural emulsifiers during lipid secretion. Additionally, hydrophobic cyclopentapeptides, malpibaldins, were structurally elucidated by NMR experiments, and their absolute stereochemistry was elucidated through chemical derivatization and synthesis. This work highlights lower fungi as a novel reservoir for natural products.
CRIS-Team Scopus Importer:2020-10-13